The Effectiveness of Mindfulness-Based Intervention Programs in Reducing the Symptoms of Anxiety in Adolescents in Indonesia - Pranatha, Aria; Kasmad, Kasmad; Rohim, Abdal; Hermansyah, Heri; Hendriana, Yana (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Anxiety is a common mental health issue among adolescents, particularly in Indonesia, where socio-cultural factors contribute to the challenges they face. Mindfulness-based interventions (MBIs) have been shown to alleviate symptoms of anxiety across various populations. This study investigates the effectiveness of MBIs in reducing anxiety symptoms among adolescents in Indonesia. The primary aim is to assess how these programs can help adolescents manage anxiety and improve their overall well-being. A mixed-methods approach was used, involving both qualitative interviews and quantitative surveys with 150 adolescents who participated in a 6-week MBI program. Pre- and post-program anxiety levels were measured using standardized tools such as the State-Trait Anxiety Inventory (STAI). The results revealed a significant reduction in anxiety symptoms among participants, indicating the potential of MBIs in promoting mental health in adolescents. The findings suggest that incorporating mindfulness practices in educational settings could be an effective approach to addressing adolescent anxiety in Indonesia. The study concludes that MBIs are a viable and beneficial intervention for reducing anxiety symptoms in adolescents, with broader implications for school-based mental health programs.